PENERAPAN PRINSIP HEALING THERAPEUTIC ARCHITECTURE DALAM PERANCANGAN WADAH PEMBELAJARAN DAN REHABILITASI KARYA WANITA DI RAWA BEBEK DENGAN METODE PERILAKU - Divina Laurentia; Mieke Choandi (Jurusan Arsitektur dan Perencanaan, 2022)
Rawa Bebek, Penjaringan sub-district, Gang Royal to be exact, is known to this day as a prostitution area mixed with densely populated houses. Even though enforcement has been carried out, it is still not complete. The residents of Rawa Bebek themselves are affected in their lives, such as children after elementary school who do not want to continue their education and are vulnerable to the negative impacts of prostitution activities. Plus there is a negative stigma against Rawa Duck. Likewise, ex-prostitute women, especially victims of exploitation who were framed, received treatment that was despised by the community. To increase their dignity, it is necessary to provide a place for rehabilitation of women's work for them to receive rehabilitation, services, and skills guidance. In addition, to reduce the negative stigma of society, awareness and education efforts are needed in the form of learning programs for self-development according to their expertise, such as non-formal learning spaces in the form of skills activities. And the gallery is also designed as a facility that can be used by the general public with material about the education of the human body. In addition, considering the condition of the population, such as children from under the village who have not received education, an equivalency education class is prepared. In the design, applying behavioral methods by paying attention to users so that the learning and rehabilitation forum for women's work is expected to be urban acupuncture in Rawa Bebek, that the community and the surrounding environment are not as bad as the stigma attached so far. Keywords: Child; Learning; Prostitution; Rehabilitation; Stigma; Teens Abstrak Rawa Bebek, daerah kelurahan Penjaringan, tepatnya Gang Royal dikenal hingga kini masih menjadi area prostitusi yang bercampur dengan rumah padat penduduk. Sekalipun telah dilakukan penertiban, namun tetap tidak tuntas. Warga Rawa Bebek sendiri terdampak dalam menjalani kehidupan, seperti anak-anak selepas SD tidak ingin melanjutkan pendidikan dan rentan terpengaruh dampak negatif dari aktivitas prostitusi. Ditambah adanya stigma negatif terhadap Rawa Bebek. Begitu pula dengan eks-wanita tuna susila terutama korban eksploitasi yang dijebak, mendapat perlakuan yang direndahkan oleh masyarakat. Untuk meningkatkan martabat mereka, perlu disediakan wadah rehabilitasi karya wanita bagi mereka untuk mendapatkan rehabilitasi, pelayanan, dan bimbingan keterampilan. Selain itu, untuk mengurangi stigma negatif masyarakat, dibutuhkan upaya penyadaran dan edukasi berupa program pembelajaran untuk pengembangan diri sesuai keahlian mereka, seperti ruang belajar nonformal dalam bentuk kegiatan keterampilan. Serta galeri juga dirancang sebagai fasilitas yang dapat digunakan masyarakat umum dengan materi mengenai edukasi tubuh manusia. Disamping itu, melihat kondisi penduduk seperti anak-anak dari kolong belum mendapat pendidikan, disiapkan kelas pendidikan kesetaraan. Dalam perancangan menerapkan metode perilaku dengan memperhatikan penggunanya sehingga wadah pembelajaran dan rehabilitasi karya wanita diharapkan menjadi akupuntur urban di Rawa Bebek, bahwa masyarakat dan lingkungan kawasan sekitarnya tidak seburuk stigma yang melekat selama ini.